Surface Enhanced Raman Scattering Spectroscopy for Pharmaceutical Determination - Tawfik A Saleh (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2016)
The rapid growth of pharmaceutical industries worldwide demands continuous development of efficient analytical techniques that help not only to detect the presence of the molecules at extremely low concentration levels, but also to detect the structure. Optical spectroscopic techniques are widely used in pharmaceutical development and manufacturing because of their speed and versatility. However, IR and Raman are relatively insensitive. Surface enhanced Raman scattering (SERS) enhances the weak Raman signal, thus, extending the range of available applications. This allows fast, sensitive detection of trace levels of key pharma molecules. However, the use of SERS for analysis requires substrates like silver nanoparticles. In this review, the applications of nano-substrates for SERS will be discussed. The synthesis and fabrication of nanocomposites; such as gold and silver, and nanocomposites will be highlighted. The characterization of the fabricated nanomaterials provide information on structures and properties that could help to improve and control their activity in SERS.